Resilience and Disability of the students of the Social Work Career of the Technical University of Manabí. - Moreira Chica, Tatiana Katiuska (2021)
Resilience in students with disabilities is of utmost importance, since it allows them to face adversities in the process of training in higher education, so they require positive environments that motivate and contribute to the achievement of their goals. The objective of this research process was to determine the resilience and type of disability of the students of the Social Work Career of the Technical University of Manabí. The development of the research was non-experimental, which was supported by the analytical, statistical, descriptive and bibliographic method; likewise, the logical-scientific method was applied: inductive-deductive, with a qualitative-quantitative approach; the survey technique was used and the survey form was used as an instrument, considering the interactive sources of resilience and the dimensions of the validated SV-RES scale, which was applied to 30 students with disabilities of the Social Work Career of the UTM. The results showed that the students under study of the Social Work Career have different types of disabilities and their resilience to face adversities is a developed capacity, since most of them claim to have resilient factors "I am, I have and I can" considering the dimensions of the validated SV-RES scale, for which they have the support of people who constitute their environment such as family, friends, classmates, teachers, Inclusion Unit, Technical University of Manabi and Welfare Programs of the Ecuadorian State.